2021
DOI: 10.5194/isprs-annals-v-3-2021-117-2021
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Assessment of Agri-Urban Land Conversion Using Multi-Sensor Remote Sensing and Gis Techniques

Abstract: Abstract. Continuous agricultural land conversion poses threat to food security but this has not been monitored due to ineffectual policies. One of the Philippine provinces with a high rate of conversion is the rice-producing province of Cavite. To assess the spatiotemporal dynamics of agricultural land conversion in Cavite, this study aims to develop an operational methodology to produce Land Use and Land Cover (LULC) change maps using a multi-sensor remote sensing approach for decision making and planning. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the study of Talukdar et al (2020), machine learning algorithms for image classification were tested which resulted in Random Forest (RF) obtaining highest accuracy of 0.89 which suggests that it is the best LULC classifier. Moreover, aside from being non-parametric and flexible to highly dimensional data, RF could produce consistent accuracies compared to other algorithms (Talukdar et al, 2020;Torbick et al, 2016;Pelletier et al, 2016;Fargas et al, 2021). However, in the study of Basheer et al (2022), SVM was reported to perform better than RF in terms of overall accuracy.…”
Section: Related Studiesmentioning
confidence: 95%
See 4 more Smart Citations
“…In the study of Talukdar et al (2020), machine learning algorithms for image classification were tested which resulted in Random Forest (RF) obtaining highest accuracy of 0.89 which suggests that it is the best LULC classifier. Moreover, aside from being non-parametric and flexible to highly dimensional data, RF could produce consistent accuracies compared to other algorithms (Talukdar et al, 2020;Torbick et al, 2016;Pelletier et al, 2016;Fargas et al, 2021). However, in the study of Basheer et al (2022), SVM was reported to perform better than RF in terms of overall accuracy.…”
Section: Related Studiesmentioning
confidence: 95%
“…The study of Fargas et al (2021) which developed an agri-urban land conversion monitoring using post classification change detection technique was also adopted in this study. Their study utilized Random Forest algorithm to produce LULC maps of their agriculture-dominant area for 3 different years and agriurban conversion was then segmented through a boolean filtering approach between the pre-and post-LULC models (Fargas et al, 2021). The boolean filtering process identified pixels classified as agricultural from the pre LULC model which were then compared to their corresponding class in the post LULC model (Fargas et al, 2021).…”
Section: Related Studiesmentioning
confidence: 99%
See 3 more Smart Citations